Risk of anaphylaxis in complementary and alternative medicine. Issue 5 (October 2017) - Gunawardana, Natasha C.
Abstract : Purpose of review: Complementary and alternative medicine (CAM) use is widespread across the world. Patients with asthma and allergy regularly use CAM therapies. Allergic and anaphylactic reactions to CAM have been reported. Recent findings: Recent attempts to regulate and monitor adverse reaction to these therapies have given us further insight into potential causes of severe allergic reactions. Several culprits identified including Andrographis paniculata, Echinacea species, bee products, Ginkgo biloba and Ginseng are discussed here. Summary: Knowing the factors that increase the risk of anaphylaxis allows reactions to be recognized, reported and further investigated. Research to identify key causative allergens is necessary in the future. Collaboration between the allergy community and CAM practitioners can allow better understanding of allergy to these therapies.